A Comprehensive Analysis of MicroRNAs in Human Osteoporosis - Huai, Ying; Zhang, Wenjuan; Chen, Zhihao; Zhao, Fan; Wang, Wei; Dang, Kai; Xue, Kaiyue; Gao, Yongguang; Jiang, Shanfeng; Miao, Zhiping; Li, Meng; Hao, Qiang; et al. (Frontiers in Endocrinology, 2020)
MicroRNAs (miRNAs) are single‐stranded RNA molecules that control gene expression in various processes, such as cancers, Alzheimer’s disease and bone metabolic diseases. However, the regulatory roles of miRNAs in osteoporosis have not been systematically analyzed. Here, we performed a comprehensive analysis to identify the differentially expressed miRNAs involved in osteoporosis. miRNAs associated with osteoporosis were collected through literature retrieval and further screened based on specific inclusion and exclusion criteria. The osteoporosis therapeutic targets of miRNAs were obtained by the integration of miRWalk 3.0 database and 5 human disease therapeutic target databases. Then, the network analysis and functional enrichment analysis of miRNAs and their targets were performed. As a result, 11 eligible miRNAs were identified highly associated with osteoporosis. miRNA-mRNA network demonstrated there were the complex mutual interactions between miRNAs and their targets. Besides, ADRB2, AR, ESR1, FGFR1, TRAF6, etc. were identified as the top hub genes in protein-protein interaction (PPI) network. Functional enrichment analysis revealed that miRNAs and their targets were mainly mapped on processes associated with bone and immune system, such as bone remolding, bone mineralization, PI3K/AKt, TNF signaling pathways and Th17 cell differentiation. RT-PCR results showed that the expression of miR-335-3p was significantly downregulated in hind limb unloading (HLU) mice tibia samples compared with controls, the remaining 10 miRNAs were significantly upregulated after HLU (P < 0.01). In summary, we identified 11 differentially expressed miRNAs in osteoporosis, which may be novel diagnostic biomarkers for osteoporosis.